An explorative study of risk management by people with disabilities : A case study in the Netherlands - Focke-Bakker, Eileen G.A.; van Gelder, Pieter H.A.J.M. (Journal of Progress in Safety & Security, 2025)
The mission and purpose of this engaged inclusive research, for and with persons with a visual- and/or hearing impairment (VI and/or HI) as experience experts, is to diminish the number of victims due to flooding. The study aims to investigate if and how these impaired persons are managing the risk of flooding in their various environments, influenced by their own background and by the ‘optimal quality’ of public authorities’ flood risk-handling. And indicate, if applicable, improvements for optimizing public authorities’ flood measures. The results show that some of the impaired respondent’s background, their public authorities’ quality assessment and their own risk management give cause for concern. Being older, living in flood sensitive land parts, and not going outside if there are too many obstacles are hindrances when the risk of flooding becomes a real incident. The impaired respondents’ family structure is not suitable for implementing the public authorities’ ‘together-reliance’ measures against flooding and their income might not be enough for flood resistance measures. Public authorities’ measures against flooding, at the national and local level, are perceived by the impaired respondents, as not optimal. Self-efficacy and respect, values of utmost importance for the impaired respondents, are, from a non- nclusive able-bodied perspective, different from that of an impaired person’s point of view. This could cause misunderstandings during flood rescue missions. Raising awareness on flooding, providing more specific information and making the information more accessible is needed. In ‘utilization of the results’, improvements are suggested. The impaired respondents capabilities of self-reliance, resilience and not privacy focused during incidents (COVID-19) could be of use. Our study added value to quality data of persons with an impairment and to the research on their flood risk management. The findings could result in less casualties and death in flooding events. One sentence summary: This study presents an explorative approach on flooding for sensory impaired persons and findings show that respondents’ background, their authorities’ quality assessment and their risk management give cause for concern.